ERROR ANALYSIS IN USING AUXILIARY CAPITAL IN WRITING (CASE STUDY OF SEMESTER III ENGLISH LITERATURE STUDENTS) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study aims to determine and identify the understanding of students in Modal Auxiliary to improve students' abilities. This research was conducted using qualitative methods. The purpose of this study is to describe the current problems related to teaching and learning of Modal Auxiliary (Auxiliary Capital) and the problem of using Auxiliary Modal by the Third semester students of English Literature, UMI Makassar. The results showed that the writing test that had been given to students was based on the problem "What mistakes did students make in using Auxiliary Modal?" and "what factors hinder students from using auxiliary capital?" When the data has been coded, and errors have been identified, the researcher classifies errors into two types, namely word crime (with a frequency of 66%), misformation (with a frequency of 34%), and the inhibiting factor, namely Students Thinking that Auxiliary Capital is difficult and Students think that Auxiliary capital is astounding. It can be said that there are errors made using certain systems, such as wrong tongue, wrong memorization, and other physical factors as well as errors made by students based on misunderstanding reasons, because students do not know, or do not understand the structure of the language.